A Analisis Komparatif Artificial Intelligence: ChatGPT, Gemini, dan Prefelixy sebagai Media Pembelajaran - Ardiansyah Ardiansyah; Abdin, Maslan; Salis, M. Rizkoni; Ardiansyah Ardiansyah, Ardiansyah Ardiansyah (Jurnal TEKNODIK, 2024)
This study aims to analyze the comparative performance of three AI platforms (ChatGPT, Gemini, and Perplexity) as learning media for Accounting 1, based on the Sub-CPMK outlined in the Semester Learning Plan (RPS). The research employs a Qualitative Comparative Analysis (QCA) method, evaluating platform responses using six criteria: accuracy, clarity, coherence, engagement, scalability, and informativeness. The results reveal that ChatGPT scored the highest (96%), followed by Gemini (92%) and Perplexity (91%). ChatGPT excels in clarity, engagement, and informativeness; Gemini shows strength in scalability, while Perplexity performs consistently in accuracy and coherence. This study highlights the importance of adaptive and collaborative AI utilization in Accounting 1 learning to enhance educational quality while ensuring ethical and secure usage.